Conceptualization and initial measurement of counseling ethics competency: the influence of spirituality and self-efficacy - Zakaria, Noor Syamilah; Subarimaniam, Neerushah; Wan Jaafar, Wan Marzuki; Mohd Ayub, Ahmad Fauzi; Saripan, M. Iqbal (Emerald Publishing Limited, 2022)
Purpose: This paper aims to contribute to the existing conceptualizations of counseling ethics competency and to develop a counseling ethics competency scale. This paper also argues that spirituality and self-efficacy influence counseling ethics competency. Design/methodology/approach: A series of studies were performed to develop hypotheses and a conceptual framework to determine the relationships among spirituality, self-efficacy and counseling ethics competency. To measure registered counselors’ counseling ethics competency, a document analysis of the Counselors Code of Ethics was conducted and pretested on the basis of a pilot test prior to the empirical development of the scale. Findings: A conceptual framework was developed to operationalize the theory and to present the influence of spirituality and self-efficacy on counseling ethics competency. The counseling ethics competency scale was found reliable and valid to measure the registered counselors’ competency in the eight components of the Counselors Code of Ethics. Practical implications: The scale and framework can be used as tools to identify competencies where registered counselors are lacking and to pinpoint skills on which counselors need to improve. This research also will provide insights for counselor educators to be innovative in teaching and learning ethics within the scope of counselor education training programs. Originality/value: There is no specific scale available to measure counseling ethics competency among registered counselors in Malaysia. Thus, this research unveils the importance of measuring counseling ethics competency in molding effective and ethical Malaysian counselors, and subsequently pinpointing factors that can improve counseling ethics competency. Recommendations: We recommend to assess the scale using EFA, followed by CFA to determine and confirm the factor structure of the scale items. In terms of the field, future scope may not just focus on the traits, characters and skills building but also place more emphasis on ethics comprehension toward best practices of ethics application and internalization on becoming self-sufficient counselors.